Asymmetries in Infants’ Attention Toward and Categorization of Male Faces: The Potential Role of Experience - Rennels, Jennifer L. (J Exp Child Psychol, 2015)
Infants typically have a preponderance of experience with females, resulting in visual preferences for female faces, particularly high attractive females, and in better categorization of female relative to male faces. We examined whether these abilities generalized to infants’ visual preferences for and categorization of perceptually similar male faces (i.e., low masculine males). Twelve-month-olds visually preferred high attractive relative to low attractive male faces within low masculine pairs only (Exp. 1), but did not visually prefer low masculine relative to high masculine male faces (Exp. 2). Lack of visual preferences was not due to infants’ inability to discriminate between the male faces (Exps. 3 & 4). Twelve-month-olds categorized low masculine, but not high masculine, male faces (Exp. 5). Infants could individuate male faces within each of the categories (Exp. 6). Twelve-month-olds’ attention toward and categorization of male faces may reflect a generalization of their female facial expertise.